Introduction to force transmission by nonlinear biomaterials. Issue 45 (10th November 2021) - Mao, Xiaoming; Shokef, Yair
Abstract : Xiaoming Mao and Yair Shokef introduce the Soft Matter themed collection on force transmission by nonlinear biomaterials.